Ремонтно-реставрационные работы в архитектурном комплексе Хансарая в 1945-1990 гг. - Османов, Э.Э. (Культура народов Причерноморья, 2013)
В данной статье проанализирована научно-исследовательская и ремонтно-
реставрационная деятельность Бахчисарайского Музея в 1945-1990 гг. Особое внимание уделено
памятникам истории и архитектуры крымских татар на территории Ханского дворца и собственно
постройкам города. Одной из первоочередных задач музея было осмотр и фиксация памятников города
и окрестностей с целью выявления разрушений после ухода нацистов. Культовые и религиозные
постройки во время оккупации использовались под хозяйственные склады, конюшни. Значительный
ущерб был нанесен всем зданиям города. К широкомасштабной реставрации дворца обратились лишь в
1961-1964 гг. Перед реставраторами стояла задача проследить все этапы переделок, выявить и
закрепить те старые элементы архитектуры и росписей, которые еще сохранились, не уничтожая при
этом и более поздних декоративных мотивов. К 1990 году коллектив музея готовился к переходу в
работе в рамках Бахчисарайского историко-культурного заповедника (БИКЗ). Была продолжена работа
по составлению карты Бахчисарайского района с обозначением памятников и их охранных зон.
Бахчисарайским Дворцом-музеем в 1920 – 90 гг. были достигнуты определенные успехи в деле
сохранения исторических памятников. В даній статті проаналізована науково-дослідна та ремонтно-реставраційна діяльність
Бахчисарайського Музею у 1945-1990 рр. Особливу увагу приділено пам'яткам історії та архітектури
кримських татар на території Ханського палацу і власне будівлям міста. Одним із першочергових
завдань музею було огляд і фіксація пам'ятників міста та околиць з метою виявлення руйнувань після
відходу нацистів. Культові та релігійні споруди під час окупації використовувалися під господарські
склади, стайні. Значний збиток був нанесений всім будівлям міста. До широкомасштабної реставрації
палацу звернулися лише в 1961-1964 рр.. Перед реставраторами стояло завдання простежити всі етапи
переробок, виявити і закріпити ті старі елементи архітектури та розписів, які ще збереглися, що не
знищуючи при цьому і пізніших декоративних мотивів. До 1990 року колектив музею готувався до
переходу в роботі в рамках Бахчисарайського історико-культурного заповідника (БІКЗ). Була
продовжена робота по складанню карти Бахчисарайського району з позначенням пам'яток та їх
охоронних зон. Бахчисарайським Палацом-музеєм в 1920 - 90 рр.. були досягнуті певні успіхи в справі
збереження історичних пам'яток. In this article we analysed the scientific-research and restoration works Bakhchsarai Museum in
1945-1990 years. Particular attention is paid to the historical and architectural monuments of the Crimean
Tatars in the Khan's palace and the actual buildings of the city. One of the primary objectives of the museum has
been inspected and fixed monuments of the city and the surrounding area in order to reveal the devastation after
the departure of the Nazis. It was revealed that the cult and religious buildings during the occupation were used
as farm warehouses, stables. Considerable damage was caused to the buildings. In order to preserve them were
provided to lay all damaged openings, cracks to shut inside. In 1954, on the basis of two museums - the "cave
towns" and the "Palace Museum" was created Bakhchisaray Historical and Archaeological Museum. For largescale
restoration of the palace turned only in 1961-1964. Before restorers were challenged to follow all the
stages of alterations, to identify and fix those old architectural elements and paintings that have survived without
destroying it and later decorative motifs. Despite carrying out repair and restoration works and expended, the
main work scheduled the Kiev workshops have not been met. For the most part, no object was ready for
excursions, while the second floor is still empty. By 1990, the staff of BHAM perfecting all aspects of the museum
and was preparing to move into the work of the Bakhchisaray Historical and Cultural Reserve (BHCR). Was
weighted list of monuments and split into groups in chronological order finalized regulations on reserve and its
structure, made maps and plotted them on the monuments, selected and conducted photographic negatives. Work
continued on the map the Bakhchisaray district designation of monuments and their protection zones. From the
above it can be concluded that the Bakhchisaray Palace Museum in 1920 - 80 years. Progress has been made in
scientific research and in the preservation of historical monuments.